2019
DOI: 10.1111/aogs.13681
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal contamination with ICG‐stained cervical secretion as surrogate for potential cervical cancer tumor cell dissemination: A proof‐of‐principle study for laparoscopic hysterectomy

Abstract: Introduction Intracorporal colpotomy during radical hysterectomy for cervical cancer is discussed to be a risk factor for peritoneal dissemination of tumor cells. It might lead to increased recurrence rates after laparoscopic radical hysterectomy compared with abdominal hysterectomy, as shown by the recent LACC study. Data on the frequency or mechanisms of peritoneal contamination are missing. We aimed to analyze peritoneal contamination of cervical secretion during intracorporal colpotomy with a novel indocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…The other potential confounding factor is peritoneal dissemination by intraoperative tumor spillage or excessive manipulation of tumor tissues 30 , 31 . We theorized that the use of a uterine manipulator during RRH might result in tumor spillage into the peritoneal cavity and combination of steep Trendelenburg position and aerosolization might have facilitated the intraabdominal seeding which leads to worse oncological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The other potential confounding factor is peritoneal dissemination by intraoperative tumor spillage or excessive manipulation of tumor tissues 30 , 31 . We theorized that the use of a uterine manipulator during RRH might result in tumor spillage into the peritoneal cavity and combination of steep Trendelenburg position and aerosolization might have facilitated the intraabdominal seeding which leads to worse oncological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient and tumor characteristics are not completely comparable between those different studies, these results raise the hypothesis that outcomes of laparoscopic radical hysterectomy depend on surgical technique and the possibility of tumor cell spread into the intraperitoneal cavity [11,12]. For example, tumor cell spread may occur during intracorporal colpotomy, when intravaginal tumor components have contact with the intraperitoneal cavity, as mechanistically demonstrated by our group [13]. In the present study, after laparoscopic surgery patients with tumors < 2 cm showed only one late recurrence after 12 years which is most likely not associated with possible intraoperative tumor cell spillage since all other local recurrences developed during the rst 1.5 years after surgery.…”
Section: Discussionmentioning
confidence: 77%
“…Nonstandardized surgical techniques and surgical inexperience are discussed as main critics of studies which show reduced survival after laparoscopic surgery. Results of various other studies lead to the hypothesis that survival might depend on failure to prevent tumor cell contamination through the use of uterine manipulators, intracorporal colpotomy or lack of vaginal cuff closure [11][12][13][14][15]. First results show that patients with tumors under 2cm or who underwent preoperative cone biopsy appear to have excellent survival even after laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal tumor exposure was an independent prognostic factor for worse survival ( 31 ). A novel fluorescence imaging‐based tool for feasible and direct visualization of peritoneal contamination during colpotomy might serve as a quality assessment tool for surgeons and surgical techniques ( 32 ). Specific measures were adopted by some surgeons to prevent tumor spillage during LRH, such as creation of a vaginal cuff, minimized handling of the uterine cervix, and bagging the specimen ( 33 ).…”
Section: Discussionmentioning
confidence: 99%